ABET accreditation Award 2012 - Markou, George (My University, 2026)
ABET accreditation Award 2012, for my contribution as an Assistant Professor in achieving the American Board for Engineering and Technology accreditation of the Civil Engineering Department of the ALHOSN University, Abu Dhabi.
Keywords: Education